2023
DOI: 10.1051/0004-6361/202244842
|View full text |Cite
|
Sign up to set email alerts
|

The Gravitational Wave Universe Toolbox

Abstract: Context. In the current multi-messenger astronomy era, it is important that information about joint gravitational wave (GW) and electromagnetic (EM) observations through short gamma-ray bursts (sGRBs) remains easily accessible to each member of the GW-EM community. The possibility for non-experts to execute quick computations of joint GW-sGRB detections should be facilitated. Aims. For this study, we constructed a model for sGRBs and added this to the framework of the previously built Gravitational Wave Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In the meanwhile, they can provide the positioning information of the GW, which increases the multi-wavelength follow-up efficiency. However, the coincidence fraction between a GW and GRB prompt emission is expected to be low, due to the highly collimated emission beam of GRB prompt emission (Hendriks et al 2022). However, if we consider the precursor and afterglow of a GRB, the coincidence fraction will increase.…”
Section: The Emc Follow-up Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…In the meanwhile, they can provide the positioning information of the GW, which increases the multi-wavelength follow-up efficiency. However, the coincidence fraction between a GW and GRB prompt emission is expected to be low, due to the highly collimated emission beam of GRB prompt emission (Hendriks et al 2022). However, if we consider the precursor and afterglow of a GRB, the coincidence fraction will increase.…”
Section: The Emc Follow-up Efficiencymentioning
confidence: 99%
“…The detection of the prompt GRB provides extra early localization and is very helpful for the host galaxy identification, wherein an independent red-shift measurement can be obtained. However, due to their highly beamed emission, the coincidence fraction between a GW and a GRB is expected to be low (Hendriks et al 2022). On the other hand, those EMCs in afterglows and kilonovae are expected to be more accessible for most of the GW signals, due to their nearly isotropic radiation distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to scientific observation runs LVC O1-O3 (Abbott et al 2019a(Abbott et al , 2023(Abbott et al , 2024 and simulative studies (such as (Hendriks et al 2023)), such a joint detection of GW/ GRB are rare (one out of ∼10 binary neutron star (BNS) merger events). In this paper, we present a simulation study on constraining v g , using GWToolbox 3 (Yi et al 2022;Hendriks et al 2023) to simulate the joint GW-GRB detection of a BNS merger event with both second and third-generation groundbased GW detectors, including aLIGO in design sensitivity (Aasi et al 2015) (design aLIGO) and Einstein Telescope (ET) (Sathyaprakash et al 2010). In comparison to similar simulative work in Nishizawa (2016), we simulated the parameterized BNS population, which is consistent with the GWTC-3 (Abbott et al 2023) catalog.…”
Section: Introductionmentioning
confidence: 99%
“…Following the practice ofHendriks et al (2023), we use the lowest observed fluence of the sGRB catalog (Narayana Bhat et al 2016) as the fluence limit of second-duration bursts. 7 https://cosi.ssl.berkeley.edu 8 https://asd.gsfc.nasa.gov/amego/ 9 https://indico.icranet.org/event/1/contributions/777/…”
mentioning
confidence: 99%